The Transformation of Buddhist Stūpas in Premodern Japan : Exploring the Symbolism of Rulership in Religious Spaces - Guo, Jianing (Universitas Negeri Surabaya, 2024)
In pre-modern Japan, Religion has always been employed to legitimize power, and its architectural manifestations have undergone changes to emphasize different nodes of authority. This paper will focus on the st?pa, a representative Buddhist architectural structure, and elaborate on its development and changes in Japan, with particular attention to the st?pa as a religious building and its temporal changes in doctrinal expression and internal structure. On this basis, I will further examine the imperial mausoleum st?pas built during the Japanese Insei period (11th to 12th centuries) and discuss how the st?pa, as a religious building, achieved its political representation by integrating with funeral rites. During the Insei period, a transitional period between the ancient and medieval periods, retired emperors conceived of their power in new ways. In particular, Retired Emperors Shirakawa and Toba had themselves interred in st?pas at Jobodaiin and Anrakujuin, respectively. This was a strange, provocative act that attempted to buttress what was then declining imperial power. The st?pa, symbolizing the Buddha's burial mound and venerating the Dainichi Nyorai, stands out for its architectural presence in the landscape. In putting their remains inside a holy space of rich resonances, Shirakawa and Toba broke precedents and constructed a novel mode of articulating rulership. Moreover, the burial of Toba in the st?pa, along with the funeral rituals he established, can be highlighted as having been perceived as a way to reinforce the authority of the Insei system.